An Analysis Of Archetypes Of Alicia Brenson In Alex Michaelides’ The Silent Patient - Safitri, Desy; Anggraeni, Diana; Arie Bowo, Tri (Loquēla (Journal of Linguistics, Literature, and Education), 2023)
This study focuses on archetypes topics on the character of Alicia in The Silent Patient novel. The purpose of this study is to examine both characterizations and archetypes of Alicia. The method employed in this study is descriptive qualitative. The data was derived from the narration and dialogue of the figures in the novel. This study uses the characterization concept of James H. Pickering & Jeffrey D. Hoeper and the theory of the archetypes by Carl Gustav Jung. The result of this archetype analysis was then highlighted by the characterization analysis of Alicia. In detail, 23 data were spotted to characterize Alicia, and each data was divided into two parts of the characterization: (1) the Telling Method (6 data from characterization through appearance, and 11 data from characterization by the author); (2) the Showing Method (3 data from characterization through dialogue, and 2 data from characterization through action). It was also found that some characterizations shown by Alicia, say coward, selfish, frustrated, cunning, liar, manipulative, unsympathetic, aggressive, violent, temperament, anxious, vengeful, cruel, arrogant, ambitious, impulsive, anger, pessimistic, unstable, and sensitive. There were 23 archetypes found in Alicia with 11 out of 23 data dominated by shadow. Then, there were 6 persona, 3 animus, and 3 self-data found in Alicia